Tissue repair in post extraction sockets of Cavia cobaya induced by a combination of propolis and graft - Utari Kresnoadi; Roselini Halim; Hananah Oktalidial Putri; Mutiara Aryanita; Imam Safari Azhar (The East Java Biological Society, 2020)
Propolis, hive defensive substance that contains caffeic acid phenethyl ester, can affect the migration and proliferation of cells involved in the healing process. Combination of propolis extract with BBG are predicted to fasten the wound healing, especially its effect on angiogenesis, macrophages and collagen density. In this study, we aimed to analyze the effect of a propolis combination and BBG in proliferating new blood vesselsand macrophages, while also increasing the collagen density of the post-extracted tooth socket healing process in Cavia cobaya. 56 C. cobaya, whose left mandibular incisorshad been extracted, were subsequently divided into four groups on the basis of the substances used to fill their sockets, namely; control, BBG, propolis extract, and a combination of BBG, and propolis extract. The subjects sacrificed on either the third or seventh day. Histopathological samples were produced using HE and MT staining. The results were subjected tosome statistical analysis tests: one-way analysis of variance (ANOVA), Tukey’s honestly significant difference (HSD), Kruskal Wallis, and Mann Whitney. Significant increases (p<0.05) were detected between the PEG and PEG+Propolis groups and also between the PEG and PEG+BBG+Propolis combination groups. However, an insignificant increase (p>0.05) was identified between the PEG and BBG groups. In conclusion, a combination of BBG and propolis can increase the number of new blood vessels and macrophages together with the degree of collagen density in the healing process of post-extraction tooth sockets of C. cobaya.